Spotting of external calibration standards on blank dried blood spots as a resource-sparing protocol. (October 2017) - Nigam, Anuja; Kole, Prashant; Kurawattimath, Vishwanath; Mandlekar, Sandhya; Subramanian, Murali
Aim: Dried blood spots (DBS) offer significant ethical and scientific advantages; however preparation of calibration curves often times, off-sets some of these advantages. We have developed a methodology wherein small volumes of external calibration standards can be spiked on to blank DBS cards.Results: A total of 2 μl of stock solution spotted on to blank blood spots yielded concentrations that were comparable to those obtained using conventional DBS method. The stability of six analytes on 10-day-old blank spots was within 80–120%. The new methodology was successfully applied to a hydroxycholorquine mouse pharmacokinetics study.Conclusion: Blank DBS samples can be opportunistically prepared from overweight or satellite animals, be stored, and subsequently spiked with standards to prepare calibration standards.